ICT Systems Security and Privacy Protection 30th IFIP TC 11 International Conference, SEC 2015, Hamburg, Germany, May 26-28, 2015, Proceedings - Federrath, Hannes; Gollmann, Dieter (IFIP Advances in Information and Communication Technology,, 2015)
This book constitutes the refereed proceedings of the 30th IFIP TC 11 International Information Security and Privacy Conference, SEC 2015, held in Hamburg, Germany, in May 2015. The 42 revised full papers presented were carefully reviewed and selected from 212 submissions. The papers are organized in topical sections on privacy, web security, access control, trust and identity management, network security, security management and human aspects of security, software security, applied cryptography, mobile and cloud services security, and cyber-physical systems and critical infrastructures security.